Unraveling the Tapestry: Filmmaker Qualifications and Their Impact on Film Quality in Telugu Cinema (International Journal of Food and Nutritional Sciences, 2019)
This research investigates the intricate connection between filmmakers' educationalqualifications and the quality of films in Telugu cinema. Utilizing a qualitative approach, datais gathered from various sources, including online platforms and personal interviews withrenowned directors.